MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPA MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA PESERTA DIDIK KELAS III SEMESTER GENAP MIN 3 BANTUL TAHUN PELAJARAN 2021/2022 - Mariyati Mariyati (Pedir Research Institut, 2022)
Abstract:. This study aims to determine the improvement of the learning outcomes of Science Subject students through the Jigsaw Type Cooperative Learning Model for Class III students of MIN 3 Bantul in the 2021/2022 academic year. The subjects in this study were grade 3 students of MIN 3 Bantul, with details of 13 female students and 13 male students. This study consisted of two cycles, each cycle consisting of 4 stages, namely, planning, implementation, observation, and reflection. Data collection techniques using observation, and tests. The results showed that student learning outcomes increased after the action was taken. The percentage of students who have not completed has decreased from cycle 1 to cycle 2 (from 28.125% to 6.25%. The percentage of students who have completed has increased from cycle 1 to cycle 2 (from 71.875% to 93.75%). Indicators of success in This research is that it is said to be successful if the percentage of students whose learning outcomes have been completed reaches a minimum of 90%. From these results, it shows that the percentage of students whose grades have completed has reached 93.75%, so this research can be said to be successful.